THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH (K3) ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT PLN INDONESIA POWER UBP BARRU DISTRICT - Fahira, Jihan; Dipoatmodjo, Tenri Sayu Puspitaningsih; Hamka, Rezky Amalia (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the influence of Occupational Safety and Health (K3) on organizational commitment with job satisfaction as an intervening variable at PT PLN Indonesia Power UBP, Barru Regency. Does Occupational Safety and Health (K3) have a positive and significant influence on organizational commitment, does Occupational Safety and Health (K3) have a positive and significant influence on job satisfaction, does job satisfaction have a positive and significant influence on organizational commitment and does job satisfaction have a positive and significant influence in mediating the influence of Occupational Safety and Health (K3) on organizational commitment. This study uses a quantitative approach with a survey method conducted on employees of PT PLN Indonesia Power UBP, Barru Regency. Data were collected through questionnaires distributed to 68 employees as samples, while the sampling method is the Slovin method and analyzed using Structural Equation Model-Partial Least Square (SEM-PLS) analysis techniques. The results of the study indicate that Occupational Safety and Health (K3) has a positive and significant influence on organizational commitment, Occupational Safety and Health (K3) has a positive and significant influence on job satisfaction, Job satisfaction has a positive and significant influence on organizational commitment, Job satisfaction has a positive and significant influence on organizational commitment, Job satisfaction has a positive and significant influence on organizational commitment, Job satisfaction has a positive and significant influence on organizational commitment,positively and significantly mediates occupational safety and health (OHS) and organizational commitment. These findings indicate that optimal OHS implementation not only creates a safe and healthy work environment but also contributes directly to increasing job satisfaction and strengthening employee commitment to the organization.Keywords: Occupational safety and health (K3), job satisfaction, organizational commitment